Phytochemical Analysis and Antifungal Activity of Ficus Sycomorus L. (Moraceae) Extracts on some Dermatophytic Fungi - Umar, L; Mansir L.; Sani MG (UMYU Journal of Microbiology Research)
Ficus sycomorus L is a large, semi-deciduous spreading savannah tree that belongs to the family (Moraceae) is used by many tribes in the treatments of skin infections. The aim of this study was to carry out phytochemical analysis and antifungal evaluation of F. sycomorus L. stem and leaf Methanol extract on some dermatophytic fungi. The stem and leaf crude extracts were obtained after drying using maceration and percolation with methanol as the solvent. The extract was subjected to qualitative phytochemical screening as well as GC-MS analysis for the presence of bioactive constituents. The antifungal inhibitory effect of the crude stem and leaf extracts was assessed by agar well diffusion methods. The phytochemical screening revealed that the leaves and stem-bark contained secondary metabolites such as tannins, flavonoids, alkaloids, saponins, reducing sugar and steroid. The GC-MS assay showed that the most prevailing compound in the methanolic stem-bark extract was 2, 9, Diazabicyclo (4, 4, 0) decane-3,10 dione, while in the methanolic leaves extract was acetic acid. The anti-dermatophytic assay of the extracts against Microsporum canis and Tricophyton tonsurans showed that the extracts inhibited the fungi with zones of inhibitions ranging from 6.33±0.47 to 24.33±0.47mm with the leaf extract exhibiting higher inhibition zones than the stem extract (p˂0.01). The study shows that both the stem and leaf methanol extract of Ficus sycomorus L possesses antifungal activity and should be considered as a potential antifungal agent in search of newer agents to address dermatophytic fungal infections